Optimization of network topology in a CIMM system used in organization management - Lewoc, Józef Bohdan; Chomiak-Orsa, Iwona; Izworski, Antoni; Skowroński, Sławomir; Kieleczawa, Antonina (Business Informatics, 2014)
CIMMs (Computer Integrated Manufacturing systems) are important systems for the overall automation of manufacturing enterprises, especially big ones. The general issues of the computer system topology were analyzed earlier. The present case study concerns the detailed design of the optimum LAN for the managerial sphere, based on the actual data for a big Polish household appliance manufacturer. For the data, the optimal LAN topology is determined, assuming the development of democratic networks. On the example of a big household appliance manufacturer, we define the first thread through the CIMM system, i.e. from the System Media tracing the costs of working media per a single appliance, via the cost accountancy up to a management subsystem. We describe the architecture of the System Media and the software architecture. We present the general scheme of the production data input and the general diagram of the cost accountancy subsystem. For the first management function of the CIMM system, we propose the accountancy information processing based on the total manufacturing costs related to individual appliances. Further development of the System Media System is discussed in short
Informatyka Ekonomiczna = Business Informatics, 2014, Nr 2 (32), s. 168-178
Keywords: automation; manufacturing; organization management; automatyzacja; produkcja; zarządzanie organizacjami